Pervaporation (PV) Separation of Methanol/Methyl Tert-butyl Ether Mixtures in Low Permeate Pressure Conditions - Ghasem Khatinzadeh; Mohammad Mahdyarfar; Ali Mehdizadeh (Journal of Petroleum Science and Technology, 2017)
Recently, pervaporation separation processes have gained much attention in the separation of azeotropic and close boiling point organic-organic mixtures due to its high separation efficiency, economy, safety, and energy saving potentials. In this work, the effects of experimental factors such as feed composition and operating temperature on the performance of a commercial poly vinyl alcohol membrane in the separation of methanol/methyl tertiary butyl ether (MTBE) mixtures at low permeate side pressures (1-20 mmHg) were evaluated. Separation factor and methanol flux significantly increased by decreasing permeate side pressure, especially to less than 5 mmHg. Therefore, the reduction of pressure from 20 to 1 mmHg at 45 °C at a feed methanol concentration of 5 wt.% increased methanol flux and separation factor from 248 to 412 g/hm2 and 73 to 211 respectively. In addition, the results indicate that by increasing feed temperature and methanol concentration in the feed, methanol flux is increased, while separation factor dropped.